Nitrile glucoside, flavonol glucoside and polyphenolic acids from Ehretia dentata Courch - Thuy, Trinh Thi; Cuong, Nguyen Huy; Sung, Tran Van (Vietnam Journal of Chemistry, 2014)
Chemical investigation of the leaves of Ehretia dentata Couch. growing in Hoa Binh, Vietnam led to the isolation and structural elucidation of a nitril glucoside, ehretioside A1, the flavonol glucoside astragalin, as well as rosmarinic acid and methyl rosmarinat. These structures were determined on the basis of MS and NMR spectroscopic data.Key words: Ehretia dentata; boraginaceae; nitrile glucoside; cyanoglucoside; astragalin; rosmarinic acid.